2020
DOI: 10.21203/rs.2.19865/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fecundity disorders in older women: declines in follicular development and endometrial receptivity

Abstract: Background : Little research is available on follicular development and endometrial receptivity in older women. This study aimed to assess follicular development and endometrial receptivity, and to evaluate ultrasonic parameters in predicting endometrial receptivity during the implantation window in older women.Methods: For this prospective case-control study, 224 older women and 215 young women were recruited. The follicular development and endometrial thickness were monitored by transvaginal ultrasound. Duri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…[8,9] Decreased ovarian function not only affects the quantity and quality of oocytes and embryos, [10] but it also may impair endometrial receptivity. [11] Decreased ovarian reserve and endometrial injury caused by abortion and endometritis after delivery may also explain reduced endometrial receptivity. Some studies have reported that the pregnancy rate and LBR of patients over 40 years old with frozen embryo transfer have increased significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8,9] Decreased ovarian function not only affects the quantity and quality of oocytes and embryos, [10] but it also may impair endometrial receptivity. [11] Decreased ovarian reserve and endometrial injury caused by abortion and endometritis after delivery may also explain reduced endometrial receptivity. Some studies have reported that the pregnancy rate and LBR of patients over 40 years old with frozen embryo transfer have increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The main reasons for the age-related decrease in oocyte and embryo quantity and quality include increased chromosomal abnormalities and apoptosis in oocytes, decreased mitochondrial number impacting function, and insufficient energy supply eventually leading to reduced oocyte number and viability [8,9] . Decreased ovarian function not only affects the quantity and quality of oocytes and embryos, [10] but it also may impair endometrial receptivity [11] . Decreased ovarian reserve and endometrial injury caused by abortion and endometritis after delivery may also explain reduced endometrial receptivity.…”
Section: Discussionmentioning
confidence: 99%